Macrobrachium rosenbergii de Man nodavirus capsid displaying Influenza A and Hepatitis B virus immunodominant regions induce humoral and cellular immune responses in mice - Yong, Chean Yeah (2015)
Hepatitis B virus (HBV) has infected one-third of the world population, where more than 350 million people infected chronically serve as HBV reservoir. It is responsible for the death of 1 million people each year. To date, vaccination remains the most effective approach to combat HBV. However, the emergence of vaccine escape mutants justified the need for a versatile system which is capable of targeting these mutants. Influenza A virus (IAV) is a highly infectious virus transmittable through air-borne droplets, which was responsible for the two wellrecorded pandamics, the Spanish flu and swine flu. Each year, approximately 3-5 million people are infected by IAV, of which 250,000-500,000 people die annually. Current influenza vaccines composed of inactivated influenza viruses, which grant protection through haemagglutinin (H) and neuraminidase (N) induced antibodies. Although highly immunogenic, H and N are prone to mutation, thereby reducing the efficacy of these glycoproteins as vaccines. Macrobrachium rosenbergii nodavirus (MrNV) is a non-zoonotic virus which infects Macrobrachium rosenbergii, commonly known as giant river prawn, causing white muscle disease (WMD). Recombinant MrNV capsid proteins produced in bacteria Escherichia coli selfassembled into non-infectious virus-like particles (VLPs). These VLPs were hypothesised to be able to display foreign epitopes for enhancing immune responses. Therefore, a common immunodominant region of HBV known as the ‘a’ determinant, and a highly conserved IAV epitope known as Matrix 2 ectodomain (M2e), were fused to the Carboxyl-terminal ends of MrNv capsid proteins. These fusion proteins harbouring polyhistidine tags at their C-terminal ends can be purified in a single-step through immobilised metal affinity chromatography (IMAC). The purified fusion proteins self-assembled into VLPs of approximately 30 nm in diameter, exposing the fused epitopes on the surface of the VLPs. Both the ‘a’ determinant and M2e displayed on the VLPs were antigenic towards antibodies specifically against HBV surface antigen (HBsAg) and Matrix 2 protein (M2) of IAV. When these fusion proteins were used for immunisation in BALB/c mice, they induced both humoral and cell-mediated immune responses specifically against the ‘a’ determinant and M2e displayed on the VLPs. Collectively, this study demonstrated that MrNV capsid protein is a novel platform for displaying foreign epitopes, be it for diagnostic assay or vaccine development.